Cerium-doped mesoporous bioactive glass nanoparticles reduce oxidative stress and adipogenic differentiation in human bone marrow-derived mesenchymal stromal cells - Jacobsen, Valentin; Kunisch, Elke; Merle, Christian; Xue, B.; Zheng, K.; Renkawitz, Tobias; Boccaccini, A. R.; Westhauser, Fabian (Journal of trace elements in medicine and biology, 2025)
Increased levels of reactive oxygen species (ROS) favor adipogenic over osteogenic differentiation in human bone-marrow derived mesenchymal stromal cells (BMSCs). Therefore, biomaterials containing ROS-suppressing elements such as Cerium (Ce) have been introduced to cell-based bone-tissue-engineering (BTE) approaches. This study was conducted to assess the efficacy of Ce-doped mesoporous bioactive glass nanoparticles (MBGNs) in reducing ROS levels and subsequently inhibiting the adipogenic differentiation of BMSCs. To this end, BMSCs were cultivated in adipogenesis inducing medium (AIM) and exposed to ions released from Ce-free MBGNs (composition in mol%: 86SiO2-14CaO), Low-Ce-MBGNs (composition in mol%: 86.6SiO2-12.1CaO-1.3CeO2) and High-Ce-MBGNs (composition in mol%: 86.0SiO2-11.8CaO-2.2CeO2). The influence of the different MBGNs on the expression of adipogenic and ROS-scavenging genes was assessed as well as their influence on lipid formation and the physical presence of ROS. Ce-MBGNs significantly reduced lipid production and the expression of adipogenic marker genes when compared to BMSCs cultivated in the presence of MBGNs or AIM alone. Furthermore, ROS levels were decreased by Ce-MBGNs alongside an upregulation of the expression of genes encoding for ROS-scavenging enzymes. Ce-MBGNs have proven their antioxidative potential. Mediated by the reduction of ROS, the undesired differentiation of BMSCs towards adipogenic lineage within BTE applications has been effectively suppressed. Ce-MBGNs target differentiation pathways in BMSCs precisely and therefore constitute an attractive biomaterial in the field of ion-based BTE.
Online verfügbar 7 February 2025, Version des Artikels 13 February 2025
Gesehen am 25.09.2025